A Qualitative-Comparative Analysis of Violent Political - Rasoul Abbasi Taghi Dizaj; Reza Hemmati (جامعه شناسی کاربردی, 2013)
Introduction By accepting this basic fact that human needs are diverse and our resources to satisfy them are limited, we can acknowledge that all communities are prone to conflict and it is, according to Simmel, an integral part of social life. Conflict, together with reconciliation, constitute forms of human community. The question is why in some countries conflict is , regulated, managed and even play an effective role in integration and social order, while in other countries it exists in a variety of mild to severe forms and is experienced through violent measures. Why do violent conflicts arise in some given communities? What are the important accessories of social cooperation, social harmony and conflict management? In the classical and contemporary theories of Marx to Dahrendorf, Collins and Turner, the most important variable in the conflict literature is inequality (Blue and Blue, 1982). According to Bangura, inequality among different social groups is a stronger source of violent conflicts in comparison to inequality between individuals. When inequality in income, wealth and access to services or political power is based on group differences, then mobilization of individuals to perform collective action considered an important issue (Bangura, 2006). As well, Mueller suggests that income inequality lead to political violence. The dissatisfaction of income distribution is a necessary precondition of collective action (Hartman & Way, 1988). Quality of democracy and quality of governance are another effective factor on conflict. As for democracy, all of its indicators have reverse and significant relationships with indicators of conflict. In other words, the more democracy is institutionalized and political rights and civil liberties improve, more reduction comes in the degree of conflict. While there is a direct relationship between inequality and social conflict, the political-economic development is also inversely related to the conflict index (Shekarchy, 1389: 176). In addition, the quality of governance has an influence on conflicts. Accountability, rule of law, control of corruption, government effectiveness, political stability, quality and regulation of affairs are the main dimensions of governance (Ibid, 135). As for the relationship between economic development and political conflict, while previous theories have emphasized that economic development, as measured by an increase in average incomes, reduces political violence, Muller challenged this notion and maintained that economic development leads to political violence (Weede, 1986).